Alcohol consumption in adolescence: the role of adolescents' gender, parental control, and family dinners attendance in an Italian HBSC sample. Issue 4 (2nd October 2021) - Perasso, Giulia; Carone, Nicola; ,; Barone, Lavinia
ABSTRACT: Parental control and family dinners attendance may constitute protective factors against alcohol consumption during adolescence, with different patterns for boys and girls, though evidence thus far have produced mixed findings. The present study analyzed Health Behaviour in School-aged Children (HBSC, 2014) data from 906 adolescents living in Northern Italy (49% boys, M years = 16.02, SD = 2.4) to examine: (a) gender differences in alcohol consumption frequency; (b) whether greater parental control would mediate gender differences in alcohol consumption over the last 30 days; (c) whether regular attendance of family dinners would strengthen the effect of parental control in decreasing adolescents' alcohol consumption, functioning differently for boys and girls. Findings indicated that boys reported to attend family dinners more regularly, to consume alcohol more frequently, and to perceive greater paternal control, than girls. Conversely, girls perceived greater maternal control than boys. Both maternal and paternal control did mediate the relation between gender and alcohol consumption, decreasing adolescents' drinking. Unexpectedly, family dinners attendance did not significantly moderate the effect of parental control on the monthly frequency of adolescents' alcohol consumption. Results underline the protective role of parental control against adolescents' alcohol consumption in both girls and boys, regardless of their family dinners attendance.